PUBLIC POLICIES OF SPORT AND LEISURE IN UBA: AN ANALYSIS FROM PELC. (Fiep Bulletin - online, 2014)
This study analyzes the public policies of sport and leisure in the town of Ubá-MG with the installation program Sport and Leisure Town managed by the National Sport, Education, Leisure and Social Inclusion, of Sports Ministry. The objective of this research was to investigate how was the installation of the program in town and throws a questioning: What were your accomplishments? What were and are the Public Policy Recreation & Sports in the town of Ubá before and after the implementation of PELC '. The methodology consists of research on books, magazines, papers and internet, as well as a field survey in the nuclei where the program was developed in the city. On the results of this research, it was concluded hat the PELC provided knowledge, socialization, learning and recreation for the participants, thus contributing to the welfare of the community ubaense. Notes with the initial findings, the ideal would be that public policy be directed to sport and leisure permanent contributing to quality of life of the people involved.
Keywords: Public Policy; PELC; Leisure